IN SILICO PREDICTION OF THE REGULATIONS OF CIART EXPRESSION AND ITS INTERACTION WITH BMAL1 - Wisnumurti, Ekapaksi
Circadian rhythm synchronizes various metabolic activities of an organism with various external changes happening within its environment. Circadian rhythm is generated by interactions between products of gene that collectively constitute the core transcriptional feedback loop. Included in this feedback loop are various transcription factors such as BMAL1, CLOCK, and other nuclear localized protein, such as PERIOD and CRYPTOCHROME. Circadian rhythm is not a standalone intracellular system, instead various environmental factor such as light and temperature also modulates the system via a vast network of intercellular and intracellular signaling system, relaying signals from the sensory organs via the nervous system. Disturbances in the core transcriptional feedback loop are the causes of various circadian disorder. CIART is one of the most recently discovered components of the circadian regulatory system. CIART interacts directly with BMAL1, one of the main components of the core transcriptional feedback loop, however the nature and details surrounding this interaction is still vague. By identifying various cis-acting regulatory elements that modulates the expression of CIART, and by studying the interaction of CIART and BMAL1 using active residue identification and molecular docking, we may shed light upon the nature of this interaction. Identification of various cis-acting elements found 2000 bp upstream from the gene that encodes CIART using MATCH shows conserved E-box sequences that indicates direct BMAL1 activity on the regulation of CIART expression. Also found several sequences that directly corresponds to sequences that functions as the binding site of several other transcription factors not directly involved in the regulation or generation of circadian rhythm, such as FOXD3, which is a known repressor heavily involved with the development of neural crest during early stages of embryonic development. These findings suggest that the expression of CIART is regulated by other components of the core transcriptional feedback loop, and its expression is heavily regulated during early stages of development. Result from active site identification shows that CIART possesses multiple interaction sites with BMAL1. These sites are located before and after the 264 residue amino acid residue of CIART. These sites facilitate the interaction of CIART with BMAL1, and inhibits the interaction of BMAL1 with histone acetyltransferase P300, due to the location of the interaction that overlaps with the interaction site of P300 with BMAL1. P300 acts as a vital component in helping BMAL1 regulates the expression of other core transcriptional feedback loop components. The result of this study can be used as a basis to further investigate the role of CIART in regulating the circadian rhythm, and to assess the potential of CIART as a target in the medication of circadian disorder.